PENGARUH MANAJEMEN HUBUNGAN PELANGGAN DAN KEWAJARAN HARGA TERHADAP LOYALITAS MEREK DIMEDIASI OLEH KEPUASAN KONSUMEN - Imas Ariastuti; Wisnu Untoro (Universitas Lambung Mangkurat, 2017)
This study examines the variables that influence people to make a decision to shop at Centro Solo Paragon. It aims to determine the effect of customer relationship management, price fairness, on the decision to shop with customer satisfaction as a mediation variable. Data collection is done by survey method through questionnaire with purposive sampling technique. The sample of research consisted of 200 respondents that is Centro Solo Paragon member who intend to be loyal to Centro Solo Paragon. Sampling is done dipublic area that is in Solo Paragon Mall. The SEM test results indicate that (1) CRM has significant influence to brand loyalty, (2) fairness of price have significant effect to brand loyalty, (3) customer satisfaction significantly influence brand loyalty, (4) CRM has significant effect to customer satisfaction, (5) price fairness significant to customer satisfaction, (6) CRM, Price fairness to brand loyalty mediating by customer satisfaction The results of this study can be used as a basis for Centro Solo Paragon in devising marketing strategies to increase sales.